2017
DOI: 10.1177/1177271917702895
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of MicroRNA-Mediated Gene Signatures and Pathways Modulating White Blood Cell Count in Childhood Acute Lymphoblastic Leukemia

Abstract: MicroRNAs (miRNAs) regulate the expression of protein-coding genes and represent potential biomarkers for childhood acute lymphoblastic leukemia (ALL). However, information linking miRNAs with their messenger RNA (mRNA) target genes modulating white blood cell (WBC) count is lacking. Here, we analyzed miRNAs and gene expression data from pediatric patients with ALL to identify a signature of miRNAs involved in ALL and their mRNA target genes, molecular networks, and biological pathways modulating WBC. We disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…More recently, however, they have been implicated in a variety of cancers, including ALL, and are increasingly recognized as potential crucial biomarkers and treatment targets 27,28 . In 2017, Ramani et al discovered signatures of differentially expressed miRNAs in ALL to better risk stratify pediatric patients and identified several dysregulated miRNA-mediated molecular networks, including VEGF, IGF-1, and JAK/STAT 29 . Additionally, Correia et al found in 2016 that downregulation of miR-146b by oncogene TAL1 promotes aggressive phenotypes of T-cell ALL (T-ALL), suggesting that exogenous miR-146b can potentially contribute to treatment strategies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, they have been implicated in a variety of cancers, including ALL, and are increasingly recognized as potential crucial biomarkers and treatment targets 27,28 . In 2017, Ramani et al discovered signatures of differentially expressed miRNAs in ALL to better risk stratify pediatric patients and identified several dysregulated miRNA-mediated molecular networks, including VEGF, IGF-1, and JAK/STAT 29 . Additionally, Correia et al found in 2016 that downregulation of miR-146b by oncogene TAL1 promotes aggressive phenotypes of T-cell ALL (T-ALL), suggesting that exogenous miR-146b can potentially contribute to treatment strategies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The resultant differentially expressed miRNAs between Austrians and Japanese were analyzed using Ingenuity Pathway Analysis (IPA) (Ingenuity Pathway Analysis: QIAGEN Inc. https://www.qiagenbioinformatics.com/products/ingenuitypathway-analysis ) 55 . Putative miRNA targets were found using Ingenuity miRNA target filter for experimentally validated and putative predicted targets (high confidence level) through in silico analysis 56 . After linking miRNAs with mRNA target genes, mRNA target genes that differed between the countries were considered.…”
Section: Methodsmentioning
confidence: 99%
“…The same study pointed out that JAK1 inhibitor ruxolitinib can rescue phenotypic changes induced by low miR-24-2 [ 134 ]. Significant downregulation of miR-25 has been also reported in pediatric ALL cases compared with healthy controls [ 59 , 62 ]. miR-24-2 belongs to a family comprising miR-92a-1, miR-92a-2 and miR-92b, whereas it is found clustered with miR-93 and miR-106b.…”
Section: Resultsmentioning
confidence: 99%